The construction of an imaginary on educational improvement: School justice and globalization - Carmen Rodríguez Martínez (Arizona State University, 2019)
The purpose of this paper is to analyze the forms assumed by the discourses on educational improvement and school justice and their relationship in shaping a global educational agenda, as well as their influence on educational reforms that are developed in different parts of the world from the eighties onwards. The basis of this study is the analysis of relevant official documents about education made by government agencies, reports of international and regional evaluations, and academic discourses supported by critical and sociological theory. The concern about quality education has come as a result of the expansion of compulsory education in Europe and especially in Latin America, in addition to the interest to achieve a competitive economy worldwide, through education. The improvement of educational quality has been claimed as a fight against exclusion and social and regional inequalities, which is possible through greater training and social cohesion. The conclusions of the article point out that inequalities have worsened and educational improvement has been colonized by economic discourse through: policies based on measurable results that constitute a neocolonialism; simplification of contents as an employment and investment strategy; and the incorporation of business management mechanisms.